Understanding Identity and Otherness in the notion of Europe in the philosophies of Arendt and Levinas - Urabayen, Julia (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
One of the most import issues in contemporary philosophy is the relationship between identity and otherness. This theme is related to the definition of Europe and of its traditions. The philosophies of Emmanuel Levinas and Hannah Arendt are a reflection on this question. Both of them share some points, but they give very different answers: Arendt chooses politics, and Levinas, ethics.